Peran Social Media Marketing Instagram Sebagai Media Komunikasi Pemasaran Dalam Meningkatkan Minat Kunjungan Wisatawan - Pradana, Bahtiar Yudha; AS, Fathor (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
The aim of this research is to find out the influence of context in increasing interest in visiting tourists at Cypress Beach in Tuban, the influence of communication in increasing interest in visiting Cypress Tuban Beach, the influence of collaboration in increasing interest in visiting Cypress Tuban Beach, the influence of connection in increasing interest in tourist visits to Tuban cypress beach. This research was conducted using quantitative methods. Meanwhile, the sampling technique uses an accidental sampling technique which is then analyzed using Structural Equation Model (SEM) analysis based on Partial Least Square (PLS).  The hypothesis of this research is: Context has an influence in increasing tourist interest in visiting Cemara Beach, Tuban. Communication has an influence in increasing tourist interest in visiting Cemara Beach, Tuban. Collaboration has an influence in increasing tourist interest in visiting Cemara Beach, Tuban. Connection has an influence in increasing tourist interest in visiting Cemara Beach, Tuban. The research conclusions of this study are (1) Context has no influence on tourist interest in visiting. (2) Communication has no influence on tourist interest in visiting. (3) Collaboration has an influence on tourist interest in visiting. (4) Connection has an influence on tourist interest in visiting.